2019
DOI: 10.1002/nau.24192
|View full text |Cite
|
Sign up to set email alerts
|

Is it time to rethink using digital palpation for assessment of muscle stiffness?

Abstract: Aim: Physiotherapists typically use digital palpation to determine residual tension in a muscle, referred to as muscle stiffness or tone. These assessments are subjective, and little is known about their accuracy or repeatability. Despite this, it is standard practice to base clinical treatment on these findings. The aim of this study was to assess physiotherapists' ability to assign a seven-point palpation scale to quantitative stiffness values generated by a novel device. Methods: Prospective observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The modified Ashworth Scale, palpation, and the pendulum test are usually used to evaluate joint stiffness clinically [ 6 , 7 ]. Although these methods have been used globally by physiotherapists because they are low cost, they have been criticized for subjective limitations and non-repeatability [ 6 , 8 , 9 ]. Shear wave elastography (SWE) also has been used to quantitatively assess muscle and tendon stiffness [ 10 , 11 ], but it requires more expensive equipment and more professional operating skills.…”
Section: Introductionmentioning
confidence: 99%
“…The modified Ashworth Scale, palpation, and the pendulum test are usually used to evaluate joint stiffness clinically [ 6 , 7 ]. Although these methods have been used globally by physiotherapists because they are low cost, they have been criticized for subjective limitations and non-repeatability [ 6 , 8 , 9 ]. Shear wave elastography (SWE) also has been used to quantitatively assess muscle and tendon stiffness [ 10 , 11 ], but it requires more expensive equipment and more professional operating skills.…”
Section: Introductionmentioning
confidence: 99%
“…21 Nonetheless, due to the subjective nature of the technique in evaluation of PFMS, it may not be as accurate as quantitative measurements. 22 Our study finding, that no relationship was identified between vaginal digital palpation and perineometer measurements, may be explained by this case. The ICS recommends manometric measures to assess PFM function.…”
Section: Discussionmentioning
confidence: 53%
“…Vaginal digital palpation is a method that is easily applicable for PFMS measurement, widely used and known to be well tolerated by patients 21 . Nonetheless, due to the subjective nature of the technique in evaluation of PFMS, it may not be as accurate as quantitative measurements 22 . Our study finding, that no relationship was identified between vaginal digital palpation and perineometer measurements, may be explained by this case.…”
Section: Discussionmentioning
confidence: 60%
“…Similar analyses have been performed as to the palpatory assessment of extra-articular soft tissues, thereby showing that even very experienced assessors are hardly able to identify the anatomical location of the target tissues [48], grade the muscle stiffness [49], pinpoint any tissue dysfunction, or tell a subject with pain from a healthy one. In some cases, even the creators of some of the methods proved inadequate [50].…”
Section: Manual Therapy: From Theoretical Speculations To Researchmentioning
confidence: 85%